Pelatihan Pemanfaatan Daun Kelor Menjadi Kelor Celup sebagai Minuman Kesehatan Tubuh di Gili Timur, Bangkalan - Wahyudi, Mohammad Arief; Septaryanto, Joko (Amalee: Indonesian Journal of Community Research and Engagement, 2020)
Abstract People of Nangkek in East Gili, Madura, have a very simple life with livelihoods as builders, porters, seasonal farmers and unemployee. Daily necessities such as vegetables are obtained by planting plants in the front or back of the house such as chillies, spinach, and Moringa trees. To satisfy needs of vegetables, they pick, for example, vegetables from Moringa leaves. It is commonly understood that Moringa leaves are very good for our bodies and brings many benefits for our healthiness. Proposers through Community Service provide training on Moringa leaves becoming a Moringa dye for body health. This activity aims to develop entrepreneurship of each household to support the development of the creative economy. The results of these activities include: 1) increasing the entrepreneurship spirit of each head of household in an effort to support the community development activities; 2) the entrepreneurial community has business planning capabilities; 3) increasing the ability of the entrepreneurial community in conducting business operations. The method used is training, assistance and evaluation that is carried out during the community service program until the partners are able to develop the business well. It is finally concluded that as the partner (homemade), they will be creative and productive for their family’s income. Keywords: Utilization, Moringa leaf packaging, Health Abstrak Masyarakat Nangkek di Gili Timur, Madura, memiliki kehidupan yang sangat sederhana dengan mata pencaharian sebagai kuli bangunan, kuli angkut, petani musiman, dan pengangguran. Kebutuhan sehari-hari seperti sayuran diperoleh dengan menanam tanaman di bagian depan atau belakang rumah seperti cabe, bayam, dan pohon kelor. Untuk memenuhi kebutuhan sayuran, mereka memilih, misalnya, sayuran dari daun kelor. Secara umum dipahami bahwa daun kelor sangat baik untuk tubuh dan membawa banyak manfaat bagi kesehatan kita. Pengusul melalui program Pengabdian kepada Masyarakat memberikan pelatihan tentang daun kelor menjadi minuman kelor celup untuk kesehatan tubuh. Kegiatan ini bertujuan untuk mengembangkan kewirausahaan setiap rumah tangga untuk mendukung pengembangan ekonomi kreatif. Hasil dari kegiatan ini meliputi: 1) meningkatkan semangat kewirausahaan setiap kepala rumah tangga dalam upaya mendukung kegiatan pengembangan masyarakat; 2) komunitas wirausaha memiliki kemampuan perencanaan bisnis; 3) meningkatkan kemampuan komunitas wirausaha dalam melakukan operasi bisnis. Metode yang digunakan adalah pelatihan, pendampingan dan evaluasi yang dilakukan selama program pengabdian masyarakat sampai para mitra mampu mengembangkan bisnis dengan baik. Akhirnya disimpulkan bahwa sebagai mitra, mereka akan kreatif dan produktif untuk pendapatan keluarga mereka. Kata kunci: Pemanfaatan, Pengemasan daun kelor, Kesehatan